Strategi Pengembangan Program Studi Komunikasi Penyiaran Islam Melalui Inovasi Kurikulum - Baidowi, Ach.; Mujahidin, Irfan; Riadi, Ahsan (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the research is to explain the strategy for developing an Islamic broadcasting communication study program. Qualitative research method through literature study. Data collection techniques with documentation and data processing with data reduction and presentation. Research results: strategies for developing the Islamic communication and broadcasting curriculum: sending professional da'wah personnel to remote areas, sending students to Islamic boarding schools to prepare professional da'wah personnel, assigning students to manage radio as a medium for da'wah, strengthening courses that lead to the Islamic broadcasting communication study program, core communication science, especially material on journalism and broadcasting, a plus da'wah-based curriculum and a balanced portion of the curriculum between theory, practice, Indonesian national qualification framework, curriculum concentration on journalism, broadcasting, public relations, plus competency in the field of counseling based on an Islamic world-view, communication technology competency and competence in managing mass media.